Traditional cultivation and management practices of agarwood (Aquilaria malaccensis) in Golaghat district of Assam (Indian Journal of Traditional Knowledge (IJTK), 2023)
A few plant species of the Thymelaeceae family are highly valuable and demanding because it contains resinous oil in their stem, branches, and roots. Agarwood (Aquilaria malaccensis) is one of them, which is found primarily in Assam and adjoining region of North Eastern parts of India as well as in other countries of South and South East India. In Assam, the plant is profusely cultivated in Golaghat, Jorhat and Sivasagar districts. Naturally, stem of the older plant is infected by fungal consortia via the holes made by stem borer. The blackish infection appears inside the stem along the line of the borer tunnel and valuable resinous oil can be extracted through water distillation from the black, infected wood. The agar oil has great demand in international market and is used in manufacturing perfume, incense stick, fragrant smoke, and pharmaceuticals industry. Since ancient time, people of this region have been cultivating Aquilaria with the methods adopted from traditional knowledge and found better success of infection and oil yield. Documentation of this traditional knowledge of Aquilaria malaccensis is of significant importance for promoting its cultivation among the people of this region before the knowledge is lost forever. The knowledge will also be useful for developing scientific method of commercial cultivation of this perennial tree. In this paper, we are discussing the traditional method of cultivation of Aquilaria malaccensis including seedling preparation, cultivation, intercropping and management practices. Agar is propagated through seeds for growing healthy seedlings; and cultivation practices of the plant are of utmost concern for harvesting valuable oil. Extensive field survey has been conducted at Golaghat district of Assam, India to document the method of cultivation and management practices of the plant. The results obtained from the field study were analyzed and interpreted for understanding the importance of this traditional cultivation practice.